2022
DOI: 10.22541/au.167052124.41804127/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards The Ultimate Brain: Exploring Scientific Discovery with ChatGPT AI    

Abstract: We introduce a powerful general probabilistic theory, GPT$^4$, that extends classical and quantum theories to include higher-dimensional probabilistic models. GPT$^4$ results from the four-fold integration of GPT in physics (General Probabilistic Theory) and GPT in AI (Generative Pretrained Transformer). In this paper, which is entirely generated by GPT$^4$, we demonstrate the capabilities of GPT$^4$ by using it to construct a new model of the universe that includes all known physical laws and phenomena. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Deep neural networks, a type of machine learning method that employs the backpropagation algorithm, have demonstrated significant success in various tasks and have even surpassed human-level performance in certain instances [9,10,11,12,13]. Such tasks include computer vision applications such as image classification, object detection, and facial recognition, as well as tasks in diverse fields such as speech recognition, recommendation systems, and gaming.…”
Section: Giving Deep Learning a Trymentioning
confidence: 99%
See 1 more Smart Citation
“…Deep neural networks, a type of machine learning method that employs the backpropagation algorithm, have demonstrated significant success in various tasks and have even surpassed human-level performance in certain instances [9,10,11,12,13]. Such tasks include computer vision applications such as image classification, object detection, and facial recognition, as well as tasks in diverse fields such as speech recognition, recommendation systems, and gaming.…”
Section: Giving Deep Learning a Trymentioning
confidence: 99%
“…Traditional methods for treating Pomacea canaliculata include pesticide development [3], importing natural enemies [4,5], and manual eradication. Recently, there has been considerable research interest in deep learning [6,7,8], which has demonstrated superior performance compared to humans in various tasks [9,10,11,12,13]. One proposed approach for the management of Pomacea canaliculata involves the use of laser rays as a potentially more energy-efficient method [14].…”
Section: Introductionmentioning
confidence: 99%